(untitled) (Northern International Medical College Journal, 2015)
Ectopic pregnancy described for the first time in the11th Century and later on it was described as pregnancy complication. Ectopic pregnancy is potentially life-threatening and remains the leading cause of maternal death. The incidence of ectopic pregnancy is increased during last years all over the world. Though Laparoscopic surgery is still the cornerstone of treatment in the majority of women, medical management is an alternative treatment option. If the diagnosis of ectopic pregnancy can be made earlier non-invasively, medical treatment with systemic intramuscular Methotrexate (MTX) aimed at reducing mortality, morbidity and reducing costs, minimal intervention/non intervention on comparing with outcomes of surgical treatment. Fertility can be preserved also. Here we presented a case of recurrent ectopic pregnancy with left adnexal mass and stable general condition was treated with MTX successfully Northern International Medical College Journal Vol.6(1) 2014: 38-39